The effect of linker DNA on the structure and interaction of nucleosome core particles - Huang, Yen-Chih (2019)
In eukaryotes, the compaction of chromatin fibers composed of nucleosome core particles (NCPs) connected by a linker DNA into chromosomes is highly efficient; however, the underlying folding mechanisms remain elusive. We used small angle X-ray scattering (SAXS) to investigate the influence of linker DNA length on the local structure and the interparticle interactions of the NCPs. In the presence of the linker DNA of 30 bp or less in length, the results suggest partial unwrapping of nucleosomal DNA on the NCP irrespective of the linker DNA length. Moreover, the presence of 15 bp linker DNA alleviated the electrostatic repulsion between the NCPs and prevented the formation of an ordered columnar hexagonal phase, demonstrating that the linker DNA plays an active role in chromatin folding.